Using Criminal Punishment to Serve Both Victim and Social Needs. - O'Hara, Erin Ann; Robbins, Maria Mayo (Law & Contemporary Problems)
Part of a special issue on group-conflict resolution. The writers propose a change to the manner in which control rights over criminal sanctions are distributed that could increase victim well-being without interfering with social needs. They assert that granting the victim the right to determine whether an offender will serve the last 10–20 percent of a prison term will not only help restore a sense of victim empowerment but will likely encourage voluntary victim-offender mediation (VOM), which has been demonstrated to assist the emotional healing process for victims while possibly decreasing recidivism rates. The writers outline recent victims' rights reform efforts and the rise in the use of VOM before presenting their proposal and considering possible objections.